L'expérience canadienne et québécoise de révision constitutionnelle : leçons et perspectives - Morin, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The author suggests various answers to two questions dealing with constitutional reform in Quebec and Canada. The first question is : What can be learned from the experience of Quebec and Canada in the field of constitutional reform ? The author makes two suggestions which underscore the following : the concern with constitutional matters has been greater in Quebec than anywhere else in Canada i.e., in part because the conception of federalism in Quebec differs from that of English-Canada, despite the use of the same words. In discussions about constitutional reform, priorities have been different for Quebec and for the rest of Canada. None of the serial discussions about constitutional reform has given Quebec the type of federalism that it wants ; Ottawa falls back upon federal official language and bilingualism policies as a placebo for an in-depth reform of federalism. The second question is : what is the present perspective for Quebec ? Here, a distinction must be made between what should be done and what could be done. What should be done includes, among other things : recognition in the Constitution of the existence in Quebec of a distinct society ; new separation of federal and provincial powers : veto right for Quebec to constitutional amendments excepting in matters regarding federal institutions ; selection of members of the Senate by the provinces. As to what could be done, let it be said that most of these reforms would probably not be accepted by the other governments in Canada because they would probably modify Canadian federalism.